1974
DOI: 10.1111/j.1751-1097.1974.tb06497.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO PHOTOREACTIVATION OF ULTRAVIOLET‐INACTIVATED RIBONUCLEIC ACID FROM TOBACCO MOSAIC VIRUS

Abstract: Abstract— Treatment of ultraviolet‐inactivated tobacco mosaic virus ribonucleic acid (TMV–RNA) with extracts obtained from the local lesion host, Nicotiana tabacum var. Xanthi, n.c., and simultaneous illumination at 365 nm results in up to a four‐fold increase in infectivity over non‐illuminated controls. The active material in the extract appears to be associated with protein, based on its inactivation by boiling, precipitation with ammonium sulfate, and exclusion from Bio‐Rad P100 polyacrylamide. Partially p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Alternatively, because transcripts exist whose half-lives span several life cycles (Herrick et al, 1990), it might be worth repairing damaged transcripts rather than discarding them. Studies from the 1970s suggested that photoreactivation might repair UV-damaged viral RNA in plants (Merriam and Gordon, 1965;Murphy and Gordon, 1971;Hurter et al, 1974). More recent work showed that alkylation damage to RNA is repaired in vivo both in bacteria and in human cells (Aas et al, 2003;Ougland et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, because transcripts exist whose half-lives span several life cycles (Herrick et al, 1990), it might be worth repairing damaged transcripts rather than discarding them. Studies from the 1970s suggested that photoreactivation might repair UV-damaged viral RNA in plants (Merriam and Gordon, 1965;Murphy and Gordon, 1971;Hurter et al, 1974). More recent work showed that alkylation damage to RNA is repaired in vivo both in bacteria and in human cells (Aas et al, 2003;Ougland et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that several DNA repair enzymes acting by direct damage reversal can also repair altered RNA. Thus, ultraviolet light-irradiated tobacco mosaic virus RNA is corrected by a host photoreactivating enzyme in plant leaf cells, catalyzing light-dependent cleavage of uracil dimers to regenerate biological activity of the viral RNA (27). The extensively investigated DNA photolyase from E. coli cleaves cyclobutane pyrimidine dimers not only in DNA, but also in RNA, and "therefore might be considered an RNA photolyase as well" (28).…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of these events may result in cell death if they exceed the capacity of repair processes. Photoproduct formation has also been demonstrated in RNA, where uracil dimers are formed by UV irradiation, again as a result of the particular susceptibility of the chromophoric n-electron structures in uracil to W radiation absorbance (Hurter et al, 1974;Kim & Sancar, 1991).…”
Section: The N-electron System and Lifementioning
confidence: 96%